Biomechanics of Acromioclavicular Joint with Clinical Relevance - Macwan, Noel Samuel; Radadiya, Tanvi (Understanding Acromioclavicular Joint Injuries and its Management, Edition 1, 2024)
The AC joint is part of the shoulder girdle, which joins the upper limb to the axial skeleton and works to coordinate the movement of the upper extremities. The synovial joint is flat, but it can move in three different planes; this limited range of motion is critical to the proper functioning of the shoulder. The articular facets are considered to be incongruent because they can be flat, reciprocally convex-convex, or inverted (reciprocally convex-concave), inverted (reciprocally convex-concave), flat, or reciprocally concave-convex. The AC capsule and ligaments offer three times the control in the anteroposterior (AP) direction than in the vertical direction. The scapula, clavicle, and related soft structures interact intimately in the biomechanics of the AC joint. In addition to the skeletal structure of the joint, the biomechanics of the joint are influenced by the CC ligaments, specifically the conoid and trapezoid, and the soft tissue elements of the AC joint capsule.